The Controversy Of The Over Granting Remissions Against Narcotics Abused During The Covid-19 Pandemic - Widodo, Joko Sri (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
The Covid-19 pandemic has a serious impact on many countries in the world, one is Indonesia. The misuse and distribution of narcotics in Indonesia has become a serious and worrying problem. Narcotics are a real threat and the eradication still requires serious handling, especially during the current Covid-19 pandemic. The implementation of massive remissions during a pandemic era like today has a lot of controversy. The legal issues that will be discussed in this paper are the controversy over granting remissions during the Covid-19 pandemic and how is the implementation of remissions to narcotics criminals during the pandemic? The research method used normative juridical research method which related to the provisions of normative law that apply in society. The results of this study show that the provision of large-scale remissions during the COVID-19 pandemic as today is controversy. This is because remission has an impact on perpetrators of abusing narcotics again. However, if remissions are not given to the prisoners, the inhabited prison will be overcapacity. This overcapacity will have an impact on ineffective services and empowerment in its implementation. This is part of a form of community-based punishment or social reintegration, namely the return of prisoners to the community, because for prisoners who get remission, it does not mean that they get a reduced sentence, but they serve the rest of their sentence outside prison. Keywords: Narchotics; Pandemic Covid-19; Prisoner; Remission